THE STUDY OF THE STIFFNESS COEFFICIENT OF THE SEAMDEPENDING ON THE QUANTITY OF SYMMETRICALLY LOCATED SHIFT ONNECTION-SIN AN OVAL TWO-LAYERPLATE - Turkov, Andrey Viktorovich; Karpova, Ekaterina (Journal of Applied Engineering Science, 2017)
The paper considers a two-layer isotropic plate on pliable connections, for which the theory of calculation of composite plates by A.R.Rzhanitsinwas adopted. With the help of bending moments Mx(My), the numerical stiffness coefficient of the seam is calculated. The numerical basic studies were carried out on an oval two-layered plate in the case of a rigid and hinged support of the plate along the contour. It proved that the stiffness coefficient of the seam ξ depends on the main coefficient after the hard oscillation frequency ω. The authors constructed the graph of the change of the natural oscillation frequency (ω) and the graph of the change of the stiffness coefficientof the seam (ξ) on the number of shift connections (nss./ne).